Sediment transport dynamics in the swash zone under large-scale laboratory conditions. (1st June 2016) - Ruju, Andrea; Conley, Daniel; Masselink, Gerd; Puleo, Jack
Abstract: A laboratory experiment was carried out to study sediment transport dynamics occurring in the swash zone of a coarse-sandy beach built in a large-scale wave flume. Hydro- and morpho-dynamic as well as sediment transport data were collected using sensors mounted on a scaffold rig deployed in the lower swash zone close to the moving bed. The high resolution of near-bed data permitted quantitative evaluation of suspended and sheet flow contributions to the total sediment transport. Although sheet flow sediment fluxes were higher than suspended fluxes, the vertically integrated suspended sediment load overcame the sheet flow load during uprush and it was on the same order of magnitude during backwash. The observed cumulative sediment transport was generally larger than the morphological changes occurring shoreward of the rig location implying either an underestimation of the offshore sediment transport or an overestimation of the onshore fluxes obtained from concentration and velocity profile data. Low correlations were found between net swash profile changes and runup parameters suggesting that local hydrodynamic parameters provide little or no predictability of accretion and erosion of an upper beach which is near equilibrium. The balance between erosion and deposition induced by individual swash events brought a dynamic equilibrium with small differences between the profiles measured at the start and at the end of the run. Abstract : Highlights: A laboratory experiment was carried out in a large-scale wave flume. Sediment transport dynamics in the lower swash zone have been analyzed. The suspended sediment load overcame the sheet flow load during uprush. The cumulative sediment transport was generally larger than the morphological changes. Low correlations were found between net swash profile changes and runup parameters.